PERTANGGUNGJAWABAN PIDANA DIREKTUR PERSEROAN TERBATAS (PT) ATAS TINDAK PIDANA PERUSAKAN LINGKUNGAN HIDUP - Aca Surya Putra Zai; Alvi Syahrin; Muhammad Hamdan; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
ABSTRACT Based on the results of this study, it can be seen that the criminal responsibility of the director as an individual for the crime of environmental destruction occurred during the director has the authority to prevent the occurrence of violations or to improve the situation. Whereas the criminal liability of the director representing the organs of a limited liability company for criminal acts of environmental destruction can be identified under the Responsible Corporate Officer Doctrine (RCO) and Strict Liability, since due to his position within the company has an obligation to take action to ensure that such violations will not occur as regulated in Article 116 and Article 117 UUPPLH. The development of the direction of criminal liability in the future in the case of criminal acts of environmental destruction has been terminated with the issuance of Perma No.13 of 2016 on the Procedures of Handling Criminal Acts by the Corporations. This regulation provides the basis for law enforcement officials, in the handling of criminal cases involving the perpetrators of corporations and / or corporate directors / administrators.   Keywords: Accountability of Director,  Limited Liability Company (PT), Crime, Environmental Degradation